Immunohistochemical analysis of GFAP expression in the experimental sepsis-associated encephalopathy - T. V. Shulyatnikova; V. O. Tumaskyi (Patologìâ)
Pathophysiology of sepsis-associated encephalopathy (SAE) is linked to blood-brain barrier breakdown, neuroinflammation and neurotransmitter imbalance in the brain. Astroglia, the most abundant cell population within the brain, plays the critical role in control of all kinds of homeostatic processes, thereby regulating the adaptive reactions of the brain to various challenges. Astroglia are highly heterogenous across the brain regions, therefore, damaging factors stimulate heterogenous astroglial reactivity and response in different brain regions.